The Relationship of Menstrual Pattern with The Incidence of Anemia in Adolescent Girls at SMA PAB 5 Klumpang, Deli Serdang in 2021 - Utary Dwi Listiarini; Indah Dewi Sari; Ani Deswita Chaniago; Efnesia Nadeak (International Archives of Medical Sciences and Public Health, 2021)
In Indonesia the percentage of women experiencing anemia increased to 48.9% with its proportion in the age group of 15-24 years. This clearly reinforces that adolescent health is crucial in the success of health development, especially in the effort to print the quality of the. This is an analytical survey research design with cross sectional approach. The sample was used purposive sampling with a total of 51 people from a population of 69 people. Sampling with non-random sampling technique used a questionnaire. Hb level test was done by using Easy Touch digital hemometer.Univariate test results of menstrual pattern based on menstrual cycles the majority of adolescents experience a normal menstrual cycle amount 27 people (47.1%), while based on the length of menstruation the majority of girls experience menstrual abnormalities amount 28 people (54.9%). The results of bivariate test with chi square test showed there was a relationship between menstrual patterns both from the menstrual cycle (p-value = .003 <.05) and menstrual time (p-value = 0.000 <.05) with the incidence of anemia in adolescent girls of SMA PAB 5 Klumpang Deli Serdang Tahun 2021.The conclusion shows that there is a significant relationship between menstrual patterns with the incidence of anemia in adolescent girls of SMA PAB 5 Klumpang Deli Serdang. It is expected that adolescent girls should pay attention to food intake and meet iron needs from natural sources.